Determining and Analyzing Corrosion Potential of Groundwater in Ghorveh through Simulating Corrosion Indices - Soraya Movahhed; Roshanak Rezaei Kalantari; Mostafa Khezri; Ali Azari (Muhandisī-i Bihdāsht-i Muḥīṭ, 2017)
Background and Objective: Scaling and corrosion are factors that cause loss of drinking water quality. They create problems for public health, reduce water quality, and decrease useful life of plumbing equipment. Therefore, their control substantially influences public health and water quality. Consequently, the present research intended to study corrosion or scaling indices of groundwater resources in Ghorveh County in Kurdistan Province using the Monte Carlo statistical method in order to reduce uncertainty and increase accuracy in estimating the values of the indices. Materials and Methods: Sixty four samples from 16 wells supplying water for Ghorveh County were taken during a 12- month period in 2012-2013 in order to study the qualitative characteristics of water and identify the corrosion and scaling potential of the water in the region using the Langelier, Ryznar, Larson-Skold, and Puckorius indices. Results: The mean values for the Langelier, Ryznar, Puckorius, and Larson-Skold indices were 0.5449±0.015, 6.8878±0.017, 7.3754±0.0078, and 0.0919±0.0390, respectively. Moreover, the estimated probabilities for the occurrence of corrosion and scaling phenomena were 6.59% and 47.57% for the Langelier index, less than 11.77% and 54.33% for the Ryznar index, less than 17.47% and 36.33% for the Puckorius index, and 0.15% and 99.74% for the Larson-Skold index. Conclusions All of the studied indices yielded identical results for the water status: they indicated a relatively high scaling potential of the water in the region. Based on Pearson’s test, the most important factors influencing the values of the studied indices were pH and concentration of calcium ions.